2014
DOI: 10.1002/smll.201303862
|View full text |Cite
|
Sign up to set email alerts
|

Gold Binary‐Structured Arrays Based on Monolayer Colloidal Crystals and Their Optical Properties

Abstract: A simple and flexible route is presented to fabricate a gold binary-structured ordered array by one step based on non-shadow deposition on a plasma etching-induced dualistic monolayer colloidal crystal. Such a Au binary-structure array is built of hexagonally arranged nanoshells and nanorings which stand between two adjacent nanoshells. Six gold nanorings surround each nanoshell. The obtained arrays exhibit both the controllable surface-plasmon-resonance (SPR) properties of Au nanoshells and the strong electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Further, TEM examination has also confirmed that the microspheres were of the truncated hollow sphere structure, as shown in Figure 10b. Only incomplete spheres were seen, similar to our previous results [29]. Obviously, such binary structured arrays are tunable in their structural parameters, such as shell thickness and curvature, ring's size, by the deposition conditions and the geometry of PS monolayer.…”
Section: Au Binary-structure Arrays From the Colloidal Template With supporting
confidence: 89%
“…Further, TEM examination has also confirmed that the microspheres were of the truncated hollow sphere structure, as shown in Figure 10b. Only incomplete spheres were seen, similar to our previous results [29]. Obviously, such binary structured arrays are tunable in their structural parameters, such as shell thickness and curvature, ring's size, by the deposition conditions and the geometry of PS monolayer.…”
Section: Au Binary-structure Arrays From the Colloidal Template With supporting
confidence: 89%
“…They were then heated on electricplate at 120 °C for 25 s and cooled naturally to room temperature (Scheme 1 b). Subsequently, 10 µL precursor solution of 0.5 M Fe(NO 3 ) 3 was dripped onto the heat-treated monolayer colloidal crystals (ca. 1 cm 2 ) with a quantitative pipette, and it could infi ltrate into the The samples full of precursor solution between colloidal monolayer and the substrate space were dried at 110 °C for 30 min, and then were annealed at 400 °C for 2 h to make the precursor decompose completely and the PSs template burnt out (Scheme 1 d).…”
Section: Methodsmentioning
confidence: 99%
“…Other non‐close packed metal NP arrays, such as Pt, Ag, and Cu NP arrays, can also be fabricated by this method . Liu and co‐workers reported the fabrication of gold binary‐structured ordered array by using a non‐shadow deposition method on a plasma etching‐induced dualistic PS monolayer arrays, as shown in Figure D …”
Section: Properties and Applications Based On The 2d Periodic Nanostrmentioning
confidence: 99%
“…Copyright 2016 Royal Society of Chemistry. (D) Au binary‐structured array and the inset shows the high‐magnification SEM images . Images reproduced with permission from Ref .…”
Section: Properties and Applications Based On The 2d Periodic Nanostrmentioning
confidence: 99%